The effects of customer and entrepreneurial orientations on individual service performance in banking sector - Acar, A. Zafer; Zehir, Cemal; Ozgenel, Nurhan; Ozsahin, Mehtap (ELSEVIER SCIENCE BV, 2013)
In recent years, there has been an increasing interest in the strategic management process which aims to achieve the performance outcomes that allow firms, including banks, to be competitive over time. This new concept requires new strategic alternatives for the companies. Today, banks need more flexible and faster organization structures to respond effectively to the customers' growing various types needs in the dynamic markets. Thus, banks use more strategic alternative tools to increase their firm performance through their employees. These tools include some strategic orientations as customer and entrepreneurship orientations. In this framework, this paper aims to examine the impact of customer orientation and entrepreneurial orientation, at the level of frontline employees in banks, on individual service performance. To reach this aim a questionnaire survey is performed. The response of 346 frontline employees in banks provides the database that was analyzed using SPSS 15 program.
Keywords: Customer orientation; Entrepreneurship orientation; Individual service performance; Financial firms; MARKET ORIENTATION; STRATEGIC ORIENTATION; CORPORATE ENTREPRENEURSHIP; ORGANIZATION STRUCTURE; LEARNING ORIENTATION; FIRM PERFORMANCE; INNOVATION; SATISFACTION; CONSTRUCT; JOB; Business & Economics; Social Sciences - Other Topics